Enhanced crude oil hydrocarbon degradation by self-immobilized bacterial consortium culture on sawdust and oil palm empty fruit bunch - Hazaimeh, Mohammad; Abd Mutalib, Sahilah; Sannasi Abdullah, Palsan; Wong, Kok Kee; Surif, Salmijah (Springer Berlin Heidelberg, 2014)
This study reports enhanced degradation of crude oil hydrocarbons by a bacterial consortium culture (CC) immobilized onto sawdust (SD) and oil palms empty fruit bunch (OPEFB). The bacterial surface hydrophobic property of the bacterial CC was 60.3 ± 2.20 %, which suggested high bacterial cell attachment onto the carrier materials. The free bacterial CC exhibited the ability to produce exopolysaccharide (EPS) in minimal salt medium (MSM). The highest value of EPS produced by free bacteria CC was 61.3 ± 2.10 %. Due to their surface hydrophobic properties and ability to produce EPS, the bacterial CC was self-immobilized onto OPEFB and SD. The immobilized bacterial CC was then used to degrade crude oil hydrocarbons. The results showed that bacterial CC immobilized onto OPEFB and SD increased degradation of crude oil by 17.52 % and, 15.85 % respectively, at week 6 of incubation, and shortened the time to complete degradation by 25 % (from 8 to 6 weeks) compared to free bacterial CC. Immobilized bacterial CC enhanced biosurfactant production, as indicated by the emulsification index (E24%). Thus, the present study demonstrated that bacterial CC immobilized onto carrier materials increases crude oil degradation by increasing production of biosurfactants.